If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1y + z = 1 Solving x + -1y + z = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. x + -1y + y + z = 1 + y Combine like terms: -1y + y = 0 x + 0 + z = 1 + y x + z = 1 + y Add '-1z' to each side of the equation. x + z + -1z = 1 + y + -1z Combine like terms: z + -1z = 0 x + 0 = 1 + y + -1z x = 1 + y + -1z Simplifying x = 1 + y + -1z
| 2(0)+y=4 | | 6(3+2x)-4=50 | | 3x^2-12y=0 | | 14n+8=-50 | | 4x=2+8x-10x+18 | | 5(5x-2)=65 | | x+9y=31 | | -9m-4=12 | | 25=1-3d | | .3b-8.4=1.5b | | x+4-3=9 | | 6=-7x-8 | | 4c-1.4=0.6 | | 0.8x-2.8=0.4 | | 5x+3=28 | | y=.25(-4)-2 | | 10+8y=16y | | 1-6x-4x=12 | | 2(a-4)+3(a+2)=3 | | (6*y)*3=6*(y*3) | | 2(a-4)+3(a+2)=16 | | 9d+sd+3d-4=5d | | 7x-8y=3 | | 17=t+8 | | 3x+5=12-y | | 4p+25=6(p-3)-3(4-3p) | | 12-5x=5x-3x+36 | | 2(4x+6)+3(2x-8)=30 | | x=2x+3 | | y=.25(4)-2 | | 25-9y=5y+11 | | X^2-3x-15=0 |